‘Sense of Place’ in Virtual Design Studio (VDS): A Review - Astrid Kusumowidagdo; Rani Prihatmanti (RUAS, 2022)
Physical design studio (PDS) and live critique sessions are essential elements in design school pedagogy. It enables students to construct their socio-spatial ability through creativity and rationality in a simultaneous way. However, due to the COVID-19 global pandemic, all teaching and learning activities must be conducted remotely in a virtual design studio (VDS). Unfortunately, VDS could be a placeless place for the students and significantly affects their overall learning experience. ‘Sense of Place’, or the people-place engagement, is an important concept in the virtual learning context from the cognitive, affective, and conative domain. VDS not merely provide the ‘place’, but should be able to support dynamic social interactions between students and the tutors as well as to conduct pedagogical activities. Without ‘Sense of Place’, the emotional and psychological engagement in creating learning experiences could not be fulfilled. This paper reviews the previous studies that concentrate on the pedagogical method and ‘Sense of Place’ in VDS at a higher education level. There are several strategies for constructing ‘Sense of Place’ in a VDS. Those are humanization, socialization, the presence of a teacher, guiding structure, graphic tools used, and the student contribution during the learning process. Another strategy is to blend both online and classroom that encourages teachings with multiple learning styles. This conceptualization of ‘Sense of Place’ in VDS is beneficial in further research with empirical data.